Pola Kepemimpinan Nyai Masriyah Amva terhadap Resiliensi Pesantren di Era Pendemi Covid -19 - Dewi Anggraeni; Fitrotul Muzayyanah; Gumilar Irfanullah (Universitas Negeri Jakarta, 2023)
The current Covid-19 pandemic has a very significant impact on the sustainability of Islamic boarding schools (pesantren). And a Nyai, as the central figure of Pesantren, is required by her distinguished leadership to continue running the education system in Pesantren. This study argues that the leadership pattern of Nyai as a female scholar in the Pesantren tradition is a factor that determines the resilience of her Pesantren during the pandemic. This study uses a phenomenological approach related to the phenomenon of the Covid-19 pandemic and responses arising from Pesantren to it. Data collection was carried out through observation, interviews, and documentation studies. This study shows that Nyai Masriyah Amva as a female scholar of Pesantren presented her Pesantren Kebon Jambu Babakan Al-Islamy as an educational institution that is embedded with values of equality. By her determinism as a female figure, Nyai Masriyah Amva's leadership formed a pattern that is egalitarian, visionary, adaptive, and responsive to such various dynamics, which determines the successful resilience of Pesantren during the Covid-19 pandemic.